Diseño de un manual de procedimiento de control interno a inventario de mercaderías de la empresa comercial Eguiguren S.A. Del Cantón Quevedo, Provincia de Los Ríos, periodo 2011 - Laaz Zambrano, Jenniffer Elisa (2012)
Commercial Company SA Tecnicentro Eguiguren, it is a private company with a long history; it founded on July 23Th, 1975 and was the first company to offer tyres, lubricants, batteries and technical service of vehicles maintenance. This present study to design a "MANUAL INTERNAL CONTROL PROCEDURES FOR INVENTORY OF MERCHANDISE FOR THE COMCERIAL COMPANY S.A. TECNICENTRO EGUIGUREN QUEVEDO BRANCH, PERIOD 2011”, which will be of great benefit to the Company will be achieved for effective control of inventory of merchandise to ensure its protection and proper use and in turn allows the collection of information financial, timeliness and reliability needed to successfully lead the management of the Agency. In the research project used several methods and research techniques, which allowed collecting all the necessary information concerning the development of processes. A diagnosis was made in the areas that are related to inventory, and these are: Sales, Service and Storage and in which it was determined that there are four processes that do not develop efficiently and effectively mainly affecting inventory control. To subsequently based on these results to develop and support the proposal of a Manual Inventory Control. With the information obtained is concluded that the proposed hypothesis, whether true: “The design of Procedures Manual for internal control is the ideal mechanism to verify the stock of goods in the Commercial Company SA Tecnicentro Eguiguren, period 2011”, so that by setting its validity can be said that all staff to implement the proposed manual and following the guidelines may contribute in a better performance y optimal control from the inventory of the Agency.